Manufacturing and application of personal hand and finger splint with three dimensional printer technology following hand and finger trauma (Annals of Medical Research, 2021)
Aim: To manufacture personal hand and finger splint with three dimensional printer, applying in emergency service patients and comparing with traditional splint applications.Material and Methods: Personal hand-finger splints were manufactured using three dimensional printer and applied to 25 patients referring to Kutahya Medical Sciences University, Faculty of Medicine, Emergency Medicine Department with upper extremity trauma and requiring hand-finger splints and these were compared with splints in the market which are medical products manufactured with traditional methods for cost, patient comfort and treatment efficiency.Results: 11 (44%) traffic accidents, 8 work accidents (32%) and 6 (24%) simple home accidents were detected in trauma etiology distribution. Based on the pathologies of the cases, 9 (36%) soft tissue pathologies, 5 (20%) proximal phalangeal, 4 (16%) distal phalangeal, 2 middle phalangeal, 3 (12%) metacarpal bone and 2 (8%) thumb fractures were found. In the controls made for all patients in the third week, it was observed that their complaints were over, they didn’t need splints anymore and there was recovery in fusion and soft tissue traumas in control x-rays. In the follow-ups of these cases, it was detected that they easily returned to their daily activities.Conclusion: In our study, personal hand-finger splints were manufactured and applied to 25 patients using 3 dimensional printer. For all cases, complete recovery was detected in the controls of all cases and fusion was provided based on control x-rays and they easily returned to their daily activities.Keywords: Finger splint; trauma; 3D printer.
Keywords: Finger splint; trauma; 3D printer.